2017
DOI: 10.1111/cen.13487
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre clinical evaluation of the new highly sensitive Elecsys® thyroglobulin II assay in patients with differentiated thyroid carcinoma

Abstract: Using appropriate assay-specific cut-offs, the clinical performance of the Elecsys® Tg II assay was comparable to that provided by the well-established Access® Tg assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Collectively, Tg is a key tool in the clinical management of DTC patient and new‐generation thyroglobulin assay performance has implications for follow‐up of DTC 13‐15 . It is worthy of attention that anti‐immunoglobulin antibodies such as TgAbs, rheumatoid factor (RF), and anti‐human animal antibodies (HAMA) are able to interfere with immunometric Tg assays 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, Tg is a key tool in the clinical management of DTC patient and new‐generation thyroglobulin assay performance has implications for follow‐up of DTC 13‐15 . It is worthy of attention that anti‐immunoglobulin antibodies such as TgAbs, rheumatoid factor (RF), and anti‐human animal antibodies (HAMA) are able to interfere with immunometric Tg assays 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the 108 patients with an indeterminate response based on b-Tg, a change to the excellent response category after s-Tg was observed in 44 %. In agreement with this finding, Brassard et al [17] showed that 41 % of 117 patients with b-Tg > 0.27 ng/ml had s-Tg < 1.4 ng/ml, Malandrino et al [19] that 36 % of 69 patients with b-Tg between 0.15 and 1 ng/ml had s-Tg ≤ 1 ng/ml, and Trimboli et al [24] that 39 % of 57 patients with b-Tg > 0.1 ng/ml had s-Tg ≤ 1 ng/ml. Even more important, the risk of recurrence in patients whose response changed from indeterminate to excellent after s-Tg was compatible with the last category.…”
Section: Discussionmentioning
confidence: 68%
“…None of the 48 patients developed recurrence, similar to the observation in patients in which both, b-Tg and s-Tg, indicated an excellent response. Despite the use of a cut off that was slightly different from the currently recommended [1-4, 12, 13], similar results have been reported by Brassard et al [17] who demonstrated recurrence in only 1/48 patients (2 %) with b-Tg > 0.27 ng/ml but s-Tg < 1.4 ng/ml; by Malandrino et al [19] who found no short-term recurrence in 25 patients with b-Tg > 0.15 ng/ml but initial US showing no tumor and s-Tg ≤ 1 ng/ ml; and by Trimboli et al [24] who did not detect disease in 22 patients with b-Tg > 0.1 ng/ml but s-Tg ≤ 1 ng/ml. Different from these results, the frequency of recurrence was 7.5 % in patients with an indeterminate response based only on b-Tg and 11 % when both, b-Tg and s-Tg, defined this category.…”
Section: Discussionmentioning
confidence: 97%
“…it difficult to assess patients transitioning from one test to another. For instance, the suggested cutoff of 0.1μg/L requires an analytical sensitivity of 0.05μg/L for the HS-Tg assay [1,5,[7][8][9], which may vary in equivalence to the Tg-ST among medical centers and laboratories [1]. A recent meta-analysis reported that while HS-Tg with a functional sensitivity of <0.1μg/L had a high negative predictive value, it lacked the accuracy and positive predictive value to provide a reliable alternative to Tg-ST [10].…”
Section: Introductionmentioning
confidence: 99%